PEMERIKSAAN PROSTATE-SPECIFIC ANTIGEN (PSA) METODE IMUNOKROMATOGRAFI PADA BERCAK CAIRAN MANI DALAM PEMBUKTIAN PERSETUBUHAN - Juli Purwo Jatmiko (Jurnal Biosains Pascasarjana, 2015)
Abstract            Sexual crime is increasing in Indonesia, both occur in big cities and rural areas who still hold traditional values, especially in societies whose economy is weak. Forensic Medicine plays a very vital in handling cases of sexual crime. One role of forensic medicine in helping to uncover cases of sexual crimes, especially rape is to prove the existence of signs of sexual intercourse, namely the discovery of the semen or sperm cells. Quite a long time interval between the time of the incident with the examination makes the process of finding sperm cells and seminal fluid becomes increasingly difficult. Examination of vaginal smears to prove the existence of ejaculate will give unsatisfactory results, since it is still possible when examination materials can be obtained from the underwear worn at the time of the incident. Current inspection methods are simple semen still have a false positive values are quite high, while the use of sophisticated methods are difficult to apply in routine services. Has recently been developed rapid test SD Bioline Cement Inspection which has a value of sensitivity and specificity that is high enough to find their prostate-specific antigen (PSA) which is one of the content in seminal fluid. With this method is expected to be an alternative in case of proof of sexual crimes.Key words: Sexual crime, prostate-spesific antigen (PSA), rapid test.